Crack evolution process of window glass under radiant heating. (31st May 2017) - Chen, Haodong; Wang, Yu; Zhang, Yi; Wang, Qingsong; Zhao, Han; Shao, Guangzheng; Su, Yanfei; Sun, Jinhua; He, Linghui
Summary: Window glass breakage has a significant impact on the compartment fire development being sometimes a weak link for fire safety design. This work focuses on the process of crack evolution of window glass in a fire environment. A total of 11 experiments were conducted in a box apparatus by changing heating rate of a heat source. The box apparatus is an enclosed compartment, which includes the heat source, assembled boxes, and glass pane. Crack time, temperature field, breaking stress, crack evolution, and fall‐out of the glass panes are presented. Main and secondary fractures are defined and illustrated in the process of crack evolution. Average time to the first, second, and third main fractures decreased as the heating rate of heat source increased. The average breaking stress was 71.14 MPa for float glass at the time of first main fracture. The crack evolution process was very complicated. Cracks initiated at an edge and propagated towards other edges for main fractures. Multiple cracks were joined together to form cracked glass islands. The fall‐out of cracked glass islands under radiant heating was more difficult than that under real fire scenarios.